Development of Proteomics in the Assessment of Genetically Modified Tomato - Prava Chhuria, Swarna; Ray, Subhalaxmi (International Journal of Psychosocial Rehabilitation, 2025)
Variations in the membrane proteome of the pericarp tomato fruit have been investigated during maturation using label-free mass spectrometry proteomics. The ' substantial equivalence ' is currently the only widely accepted criterion to assess whether or not a transgenic crop is in food view, fully consistent with the ' traditional ' food from which it is derived. Even though, there is no exact comparison defined which deals with the comparison between the chemical compositions of the two foods. One of the most suited methods for the simultaneous screening of many components without previous identification, proteome analysis, can be used for a more in-depth analysis. Food security, with the provision of food to 9 billion people in 2050, is a key global challenge in plant biotechnology. New crop species must be tolerant of environmental stresses caused by climate change, better yields, more nutrition and less resource consumption to achieve this change in agricultural production. In order to supply these new crop varieties, genetic changes and marker-assisted screening are necessary along with the system level characterization that is important for evaluating these varieties both in terms of food safety and the efficient designing of traits. For the shotgun proteomics of tomato fruit, an optimized protocol was developed, which is a re-calcitrant tissue due to a high percentage of sugars and secondary metabolites.